Uji Aktivitas Antimikroba Ekstrak Etanol Kulit Bawang Merah (Allium cepa L.) dengan Metode Difusi Cakram - Octaviani, Melzi; Fadhli, Haiyul; Yuneistya, Erenda (UI Scholars Hub, 2019)
Shallots (Allium cepa L.) are generally used as cooking ingredients by the community. The part of the shallot widely used is only a part of the tuber, while the outer shell of the shallot is thrown away because it is only considered as wastes. Based on phytochemical screening results, extract of shallot peels contains phenolics, flavonoids, and terpenoids that can inhibit the growth of microorganisms. The purpose of this research is to know the antimicrobial activity of ethanol extract of shallot peels against Staphylococcus epidermidis and Staphylococcus aureus as Gram positive bacteria, Salmonella thypi and Eschericia coli as Gram negative bacteria and also antifungal activity against Trichophyton mentagrophytes. The study was performed using disc diffusion method with the variation of concentration of ethanol extract of the peels of 50%, 25%, 12.5%, 6.25%, 3.125% and 1.5625% w/v, respectively, the positive control of chloramphenicol for bacteria, the positive control of nystatin for fungi and the negative control of DMSO. The diameter of the inhibition zone formed on the activity assay of ethanol extract of the shallot peels against Staphylococcus epidermidis, Staphylococcus aureus, Salmonella thypi and Eschericia coli at the concentration of 50% was 11.75 mm, 16.03 mm, 9.42 mm and 7.77 mm, respectively. The inhibition zone formed on the activity assay of ethanol extract of the shallot peels against Trichophyton mentagrophytes at the concentration of 50% was 18.53 mm. As conclusion, ethanol extract of the shallot peels could inhibit the growth of Staphylococcus aureus, Staphylococcus epidermidis, Salmonella thypi, Escherichia coli and Trichophyton mentagrophytes.